2009
DOI: 10.1093/molehr/gap083
|View full text |Cite
|
Sign up to set email alerts
|

Genomic changes detected by array CGH in human embryos with developmental defects

Abstract: Developmental abnormalities of human embryos can be visualized in utero using embryoscopy. Our previous embryoscopic and genetic evaluations detected developmental abnormalities in the majority of both euploid (74%) and aneuploid or polyploid (90%) miscarriages. Since we found the pattern of morphological changes to be similar in euploid and non-euploid embryos, we proposed that lethal submicroscopic changes, not detected by standard chromosome testing, may be responsible for miscarriage of euploid embryos. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…6e10, 18 Recently, two studies showed that potentially pathogenic CNVs were present in 6e15% of POC samples by analyzing the content and function of certain genes within CNVs. 5,15 Another study using SNP array to investigate a large-scale cohort of POC samples revealed potentially pathogenic CNVs in 1.6% of cases. 12 However, at present, because data about clinical significance of most CNVs were determined through genotypeephenotype correlation of individuals with clinical features, it was difficult to define whether or not CNVs were pathogenic in most POC specimens without any recognizable phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6e10, 18 Recently, two studies showed that potentially pathogenic CNVs were present in 6e15% of POC samples by analyzing the content and function of certain genes within CNVs. 5,15 Another study using SNP array to investigate a large-scale cohort of POC samples revealed potentially pathogenic CNVs in 1.6% of cases. 12 However, at present, because data about clinical significance of most CNVs were determined through genotypeephenotype correlation of individuals with clinical features, it was difficult to define whether or not CNVs were pathogenic in most POC specimens without any recognizable phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Unique CNVs were defined as those that showed no or incomplete overlap with CNVs in the DGV, or that are presented in the DGV, but with < 100 cases studied and/or a frequency of < 1%. 5,15 The building of the human genome assembly was based on GRCH37/hg19. Unique CNVs were assessed by searching for similar cases in DECIPHER and PubMed, and also by searching for gene information in Entrez Gene and OMIM.…”
Section: Snp Array Analysismentioning
confidence: 99%
“…For the validation of two maternally inherited abnormalities (duplications of 1p34.1 and 20q13.12), for which FISH testing was not possible, custom arrays were designed using eArray (Agilent technologies) and the ADM-2 algorithm as described previously (Rajcan-Separovic et al 2010). …”
Section: Custom Oligonucleotide Array Cghmentioning
confidence: 99%
“…Despite the clear association of abnormal karyotypes and embryogenesis, it is noteworthy that a signifi cant proportion of early failed pregnancies with developmental defects are karyotypically normal. Studies suggest that up to ~20 % of morphologically abnormal embryos possess a normal karyotype (Philipp et al 2003 ;Rajcan-Separovic et al 2010 ). It seems plausible that many of these seemingly euploid developmentally abnormal embryos may be the result of submicroscopic perturbations that are not detectable by routine karyotyping.…”
Section: Genomic Structural Aberrationsmentioning
confidence: 99%
“…However, the consequence of these submicroscopic aberrations on fertilization, embryogenesis, and fetal development remains poorly understood. To date, a handful of studies have reported that between 4 and 13 % of miscarriages may possess submicroscopic chromosome aberrations that would not be detectable by routine karyotyping (Rajcan-Separovic et al 2010 ;Shaffer et al 2008 ;Shimokawa et al 2006 ). It is important to note that the majority of studies did not determine whether these submicroscopic alterations were de novo, benign, or potentially pathogenic.…”
Section: Genomic Structural Aberrationsmentioning
confidence: 99%